Economy-wide effects of El Niño / Southern Oscillation (ENSO) in Mexico and the role of improved forecasting and technological change - Harris, Rebecca Lee; Robinson, Sherman (International Food Policy Research Institute, 2001)
Weather fluctuations, such as those caused by the El Niño Southern Oscillation (ENSO), add to the riskiness associated with agricultural production. Improved predictive capacity may help ameliorate negative impacts of climate and weather shocks on agriculture, but it is possible that the benefits of an improved forecast will be distributed unevenly. In particular, poor farmers may not have access to improved forecasts, or they may not have the means to adapt to new weather information. This paper uses a stochastic computable general equilibrium (CGE) model to examine the distributive effects of improved forecasting of ENSO in Mexico. The particular focus is on agriculture, one of the most vulnerable sectors in the face of ENSO, as well as a sector which provides income to many of the country's poorest households. The model is used to investigate the responsiveness of various sectors of the economy under different degrees of improved predictive capacity and improvements in agricultural technology....The results show that while agricultural losses are small as a share of the overall economy, improved forecasting techniques can eliminate these losses